Phase change temperature control polyurethane material and preparation method thereof
Modified vanadium dioxide is prepared by reacting premodified vanadium dioxide with N,N-dimethyl-4-nitrosoaniline and polymerizing with borosiloxane oligomer and isophorone diisocyanate. Functional polyurethane is obtained to form phase change temperature-controlled polyurethane materials, which solves the problems of aging and high energy consumption of polyurethane materials, and achieves efficient anti-aging, mechanical performance improvement and energy conservation effects.
Patent Information
- Application Number
- CN202510047232.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2045-01-13
AI Technical Summary
Existing polyurethane materials are prone to aging during long-term use, affecting the service life of windows, and it is difficult to effectively regulate sunlight and indoor temperature, resulting in high energy consumption.
Modified vanadium dioxide is prepared by reacting premodified vanadium dioxide with N,N-dimethyl-4-nitrosoaniline and polymerizing with borosiloxane oligomer and isophorone diisocyanate. Functionalized polyurethane is obtained to form a phase change temperature-controlled polyurethane material. This material is made by molding technology and has excellent anti-aging, mechanical properties and antibacterial properties.
It has achieved efficient anti-aging and improved mechanical properties of polyurethane materials, and has self-healing and antibacterial functions. At the same time, through the phase change temperature control effect of vanadium dioxide, it can effectively adjust the indoor temperature and reduce energy consumption.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a phase-change temperature-controlling polyurethane material and a preparation method thereof. Background Art
[0002] In recent years, with the development of industry and the growth of population, energy consumption has also increased rapidly worldwide. It is reported that in developed countries, building energy consumption accounts for about 40% of total energy consumption, which is higher than the energy consumption of industry and transportation, and more than half of building energy consumption is used for heating, ventilation and air conditioning. Reducing energy consumption and improving energy efficiency are becoming increasingly important. Windows are considered to be the least energy-efficient part of a building because the heat transfer direction of windows is from outside to inside, which is opposite to the direction of people's need to dissipate heat to the outdoors. Smart windows respond to external stimuli in a dynamic and reversible way to adjust the intensity of sunlight entering the room and the incident energy of the sun. Compared with ordinary glass windows, smart windows can not only ensure indoor lighting, but also adjust the impact of sunlight on indoor temperature under certain conditions, providing a feasible solution for building energy conservation.
[0003] Polyurethane is a polymer material used in the production of doors and windows. It will age under long-term exposure to wind, sun and rain, which will affect the service life of the windows. Therefore, it is necessary to prepare a phase-change temperature-control polyurethane material with excellent anti-aging performance, which can save energy and control temperature while extending the service life of the material. Summary of the invention
[0004] The object of the present invention is to provide a phase-change temperature-control polyurethane material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A phase-change temperature-controlling polyurethane material, wherein the phase-change temperature-controlling polyurethane material is prepared by reacting pre-modified vanadium dioxide and N,N-dimethyl-4-nitrosoaniline to obtain modified vanadium dioxide; polymerizing borosiloxane oligomer, 1,6-hexanediol and isophorone diisocyanate to obtain functionalized polyurethane; and uniformly mixing the functionalized polyurethane and the modified vanadium dioxide, and performing compression molding to obtain the phase-change temperature-controlling polyurethane material. The pre-modified vanadium dioxide is prepared by reacting vanadium dioxide and 4-anilinotriethoxysilane; The borosiloxane oligomer is prepared by polymerizing phenylboric acid and 3-chloropropylmethyldimethoxysilane and capping with 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane.
[0006] As an optimization, the preparation method of the phase-change temperature-controlling polyurethane material comprises the following preparation steps: (1) Pre-modified vanadium dioxide, glacial acetic acid, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(0.6-0.8):(40-50), and ultrasonically dispersed for 20-30 min. N,N-dimethyl-4-nitrosoaniline (3-4 times the mass of the pre-modified vanadium dioxide) was added, and stirred at 50-54°C and 200-300 r / min for 4-5 h. The mixture was filtered, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 70-80°C under vacuum conditions for 9-10 h to obtain modified vanadium dioxide. (2) Add phenylboric acid and 3-chloropropylmethyldimethoxysilane in a molar ratio of 1:(1.2~1.3) to 1,4-dioxane (14~16 times the mass of phenylboric acid), stir and react at 79~81°C and 200~300r / min for 50~60min, add a capping agent (0.11~0.13 times the mass of 3-chloropropylmethyldimethoxysilane), continue stirring and reacting for 8~10min, cool to room temperature, wash with an equal volume of toluene and deionized water, stand for stratification, take the organic phase, and dry it at 50~60°C under vacuum conditions for 8~10h to obtain borosiloxane oligomer; (3) Mix borosiloxane oligomer, 1,6-hexanediol, dibutyltin dilaurate and butanone evenly, stir at 10-30°C and 100-200 r / min for 10-12 min, heat to 76-78°C, add isophorone diisocyanate in an amount of 2-2.2 times the mass of borosiloxane oligomer, continue stirring and reacting for 4-5 h, add anhydrous ethanol in an amount of 1-1.2 times the mass of isophorone diisocyanate, mix evenly, continue stirring for 5-7 min, and dry at 68-70°C under vacuum conditions for 10-12 h to obtain functionalized polyurethane; (4) Add functionalized polyurethane and modified vanadium dioxide into an internal mixer at a mass ratio of 1:(0.03-0.05), stir at 180-190°C and 60-80 r / min for 6-8 min, place in a molding machine for compression molding, cool to room temperature and then demold, to obtain a phase change temperature-controlled polyurethane material.
[0007] As an optimization, the preparation method of the pre-modified vanadium dioxide in step (1) is as follows: vanadium dioxide and anhydrous ethanol are mixed uniformly in a mass ratio of 1:(60~70), ultrasonically dispersed for 1.2~1.4h, 7~8 times the mass of vanadium dioxide is added with anilinosilane hydrolyzate, stirred at 50~60°C and 100~200r / min for 2~2.2h, filtered, washed with anhydrous ethanol for 3~5 times, and dried at 60~70°C under vacuum conditions for 9~10h to obtain pre-modified vanadium dioxide.
[0008] As an optimization, the particle size of the vanadium dioxide is 2000 mesh, and the manufacturer is Qinghe County Chaotai Metal Materials Co., Ltd.
[0009] As an optimization, the preparation method of the anilinosilane hydrolyzate is: 4-anilinotriethoxysilane and deionized water are mixed evenly in a mass ratio of 1:(20~22), stirred at 10~30°C and 100~200r / min for 10~12min, adjusted the pH to 5.6~5.8 with an oxalic acid aqueous solution, and continued stirring for 20~30min to prepare anilinosilane hydrolyzate.
[0010] As an optimization, the concentration of the oxalic acid aqueous solution is 1 mol / L.
[0011] As an optimization, the capping agent in step (2) is: 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane.
[0012] As an optimization, the mass ratio of the borosiloxane oligomer, 1,6-hexanediol, dibutyltin dilaurate and butanone in step (3) is 1:(0.2-0.3):(0.03-0.05):(8-10).
[0013] As an optimization, the process parameters of the compression molding in step (4) are as follows: setting the temperature of the upper and lower mold plates of the compression molding machine to 200-210°C, the pressure to 14-16 MPa, and the time to 7-9 min.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the phase-change temperature-controlling polyurethane material, the present invention comprises the following steps: reacting vanadium dioxide and 4-anilinotriethoxysilane to obtain pre-modified vanadium dioxide; reacting the pre-modified vanadium dioxide and N,N-dimethyl-4-nitrosoaniline to obtain modified vanadium dioxide; polymerizing phenylboric acid and 3-chloropropylmethyldimethoxysilane, and end-capping with 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane to obtain borosiloxane oligomer; polymerizing the borosiloxane oligomer, 1,6-hexanediol and isophorone diisocyanate to obtain functionalized polyurethane; and uniformly mixing the functionalized polyurethane and the modified vanadium dioxide, and performing compression molding to obtain the phase-change temperature-controlling polyurethane material.
[0015] Firstly, vanadium dioxide and 4-anilinotriethoxysilane are reacted to obtain pre-modified vanadium dioxide, and aniline groups are introduced on the surface of the pre-modified vanadium dioxide; the aniline groups introduced on the surface of the pre-modified vanadium dioxide undergo Mills reaction with the nitroso groups on N,N-dimethyl-4-nitrosoaniline to obtain modified vanadium dioxide, an azobenzene structure is generated on the surface of the modified vanadium dioxide, and a tertiary amine structure is introduced; the azobenzene structure is transformed from a trans conformation to a cis conformation under the action of ultraviolet light, and can be observed at wavelengths greater than 440nm. When exposed to light, it will change from cis conformation to trans conformation. This reversible conformational change can absorb ultraviolet light, giving the phase-change temperature-control polyurethane material excellent anti-aging properties. The tertiary amine structure introduced on the surface of the modified vanadium dioxide can react with the chlorine atoms introduced on the side chains of the functionalized polyurethane molecules to form a quaternary ammonium salt structure, so that a cross-linked structure is formed between the polyurethane molecular chain and the modified vanadium dioxide, which inhibits the relative slip between the polyurethane molecular chains and improves the mechanical properties of the phase-change temperature-control polyurethane material. At the same time, the generated quaternary ammonium salt structure has It has an antibacterial effect and can give phase-change temperature-control polyurethane materials excellent antibacterial properties; vanadium dioxide is a thermochromic material that undergoes a reversible phase change at 68°C, from an insulating monoclinic phase to a metallic rutile phase, and at the same time, the optical and electrical properties change dramatically, and the infrared transmittance changes from a high transmittance at low temperature to a high reflectivity at high temperature, showing excellent infrared region regulation capabilities. When glass windows are produced with phase-change temperature-control polyurethane materials, the requirements of indoor warmth in winter and coolness in summer can be achieved, greatly reducing the energy consumption caused by indoor heating in winter and cooling in summer; and the visible light transmittance of vanadium dioxide remains basically unchanged during the phase change process, and still maintains a high visible light transmittance, which can provide sufficient lighting for buildings; vanadium dioxide is an inorganic material and has poor compatibility with organic polymer material polyurethane. Direct addition will result in uneven distribution and agglomeration of vanadium dioxide. Surface modification of vanadium dioxide is performed to improve the compatibility of vanadium dioxide with polyurethane, so that vanadium dioxide is evenly dispersed in polyurethane, and the phase change temperature control effect of vanadium dioxide is fully exerted.
[0016] Secondly, phenylboric acid and 3-chloropropylmethyldimethoxysilane are polymerized and terminated with 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane to obtain a borosiloxane oligomer, a Si-OB structure is introduced into the main chain of the borosiloxane oligomer molecule, a chlorine atom is introduced into the side chain of the borosiloxane oligomer molecule, and a hydroxyl group is introduced into both ends of the borosiloxane oligomer molecular chain; the hydroxyl groups introduced into both ends of the borosiloxane oligomer molecular chain enable it to participate in the polymerization reaction of polyurethane; the borosiloxane oligomer, 1,6-hexanediol and isophorone diisocyanate are polymerized to obtain a functionalized polyurethane; the Si-OB structure is introduced into the main chain of the functionalized polyurethane molecule, and the Chlorine atoms are introduced into the side chains of functionalized polyurethane molecules; boron atoms of Si-OB in the main chain can form boron-oxygen coordination bonds with oxygen atoms in adjacent molecular chains. The boron-oxygen coordination bonds are a kind of dynamic reversible bonds. Boron atoms with vacancies act as receptors for lone electron pairs of oxygen atoms in adjacent molecular chains, forming non-bonded complexes between molecules. The interaction between boron and oxygen atoms causes dynamic physical crosslinking between molecular chains. This bonding is in a dynamic process of continuous dissociation and reformation, which makes the phase-change temperature-control polyurethane material have self-healing properties. The formation of boron-oxygen coordination bonds also causes physical crosslinking between polyurethane molecular chains, further improving the mechanical properties of the phase-change temperature-control polyurethane material. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0018] A method for preparing a phase-change temperature-controlling polyurethane material, the method comprising the following preparation steps: (1) 4-anilinotriethoxysilane and deionized water were mixed at a mass ratio of 1:20, stirred at 10°C and 100 r / min for 12 min, and the pH was adjusted to 5.6 with a 1 mol / L oxalic acid aqueous solution. The mixture was stirred for 30 min to prepare an anilinosilane hydrolyzate. Vanadium dioxide and anhydrous ethanol were mixed at a mass ratio of 1:60, ultrasonically dispersed for 1.2 h, and anilinosilane hydrolyzate with a mass of 7 times that of vanadium dioxide was added. The mixture was stirred at 50°C and 100 r / min for 2.2 h, filtered, and The pre-modified vanadium dioxide was prepared by washing with anhydrous ethanol for 3 times, and drying at 60°C for 10 hours under vacuum conditions. The pre-modified vanadium dioxide, glacial acetic acid, and N,N-dimethylformamide were mixed evenly at a mass ratio of 1:0.6:40, and ultrasonically dispersed for 20 minutes. N,N-dimethyl-4-nitrosoaniline, which was 3 times the mass of the pre-modified vanadium dioxide, was added, and stirred at 50°C and 200r / min for 5 hours, filtered, and washed with anhydrous ethanol and deionized water for 3 times each, and dried at 70°C for 10 hours under vacuum conditions to obtain modified vanadium dioxide. (2) Add phenylboric acid and 3-chloropropylmethyldimethoxysilane in a molar ratio of 1:1.2 to 1,4-dioxane (14 times the mass of phenylboric acid), stir and react at 79°C and 200 r / min for 50 min, add 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane (0.11 times the mass of 3-chloropropylmethyldimethoxysilane), continue stirring and reacting for 10 min, cool to room temperature, wash with an equal volume of toluene and deionized water, stand and separate, take the organic phase, and dry it at 50°C for 10 h under vacuum conditions to obtain borosiloxane oligomer; (3) Mix borosiloxane oligomer, 1,6-hexanediol, dibutyltin dilaurate and butanone in a mass ratio of 1:0.2:0.03:8, stir at 10°C and 100 r / min for 12 min, heat to 76°C, add isophorone diisocyanate twice the mass of borosiloxane oligomer, continue stirring and react for 5 h, add anhydrous ethanol once the mass of isophorone diisocyanate, mix evenly, continue stirring for 7 min, and dry at 68°C under vacuum for 12 h to obtain functionalized polyurethane; (4) Functionalized polyurethane and modified vanadium dioxide were added into an internal mixer at a mass ratio of 1:0.03, stirred at 180°C and 60 r / min for 8 min, and placed in a molding machine for compression molding. The upper and lower mold plate temperatures of the molding machine were set to 200°C, the pressure was set to 14 MPa, and the molding time was set to 9 min. After cooling to room temperature, the mold was demolded to obtain a phase change temperature-controlled polyurethane material. Example 2
[0019] A method for preparing a phase-change temperature-controlling polyurethane material, the method comprising the following preparation steps: (1) 4-anilinotriethoxysilane and deionized water were mixed at a mass ratio of 1:21, stirred at 20°C and 150 r / min for 11 min, and the pH was adjusted to 5.7 with a 1 mol / L oxalic acid aqueous solution. The mixture was stirred for 25 min to prepare an anilinosilane hydrolyzate. Vanadium dioxide and anhydrous ethanol were mixed at a mass ratio of 1:65, ultrasonically dispersed for 1.3 h, and anilinosilane hydrolyzate (7.5 times the mass of vanadium dioxide) was added. The mixture was stirred at 55°C and 150 r / min for 2.1 h, filtered, and washed with anhydrous ethanol. The pre-modified vanadium dioxide was washed with water and ethanol for 4 times, and dried at 65°C for 9.5 hours under vacuum conditions to obtain pre-modified vanadium dioxide; the pre-modified vanadium dioxide, glacial acetic acid, and N,N-dimethylformamide were mixed evenly at a mass ratio of 1:0.7:45, and ultrasonically dispersed for 25 minutes, and 3.5 times the mass of the pre-modified vanadium dioxide was added with N,N-dimethyl-4-nitrosoaniline, and stirred at 52°C and 250r / min for 4.5 hours, filtered, washed with anhydrous ethanol and deionized water for 4 times each, and dried at 75°C for 9.5 hours under vacuum conditions to obtain modified vanadium dioxide; (2) Add phenylboric acid and 3-chloropropylmethyldimethoxysilane in a molar ratio of 1:1.25 to 1,4-dioxane (15 times the mass of phenylboric acid), stir and react at 80°C and 250 r / min for 55 min, add 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane (0.12 times the mass of 3-chloropropylmethyldimethoxysilane), continue stirring and react for 9 min, cool to room temperature, wash with an equal volume of toluene and deionized water, stand and separate, take the organic phase, and dry it at 55°C under vacuum for 9 h to obtain borosiloxane oligomer; (3) The borosiloxane oligomer, 1,6-hexanediol, dibutyltin dilaurate and butanone were mixed in a mass ratio of 1:0.25:0.04:9, stirred at 20°C and 150 r / min for 11 min, heated to 77°C, added with isophorone diisocyanate in an amount 2.1 times the mass of the borosiloxane oligomer, continued to stir and react for 4.5 h, added with anhydrous ethanol in an amount 1.1 times the mass of the isophorone diisocyanate, mixed evenly, continued to stir for 6 min, and dried at 69°C under vacuum conditions for 11 h to obtain a functionalized polyurethane; (4) Functionalized polyurethane and modified vanadium dioxide were added into an internal mixer at a mass ratio of 1:0.04, stirred at 185°C and 70 r / min for 7 min, and placed in a molding machine for compression molding. The upper and lower mold plate temperatures of the molding machine were set to 205°C, the pressure was set to 15 MPa, and the molding time was set to 8 min. After cooling to room temperature, the material was demolded to obtain a phase change temperature-controlled polyurethane material. Example 3
[0020] A method for preparing a phase-change temperature-controlling polyurethane material, the method comprising the following preparation steps: (1) 4-anilinotriethoxysilane and deionized water were mixed at a mass ratio of 1:22, stirred at 30°C and 200 r / min for 10 min, and the pH was adjusted to 5.8 with a 1 mol / L oxalic acid aqueous solution. The mixture was stirred for 30 min to prepare an anilinosilane hydrolyzate. Vanadium dioxide and anhydrous ethanol were mixed at a mass ratio of 1:70, ultrasonically dispersed for 1.4 h, and anilinosilane hydrolyzate 8 times the mass of vanadium dioxide was added. The mixture was stirred at 60°C and 200 r / min for 2 h, filtered, and Wash with anhydrous ethanol for 5 times, dry at 70°C for 9 hours under vacuum conditions to obtain pre-modified vanadium dioxide; mix the pre-modified vanadium dioxide, glacial acetic acid and N,N-dimethylformamide at a mass ratio of 1:0.8:50, ultrasonically disperse for 30 minutes, add N,N-dimethyl-4-nitrosoaniline 4 times the mass of the pre-modified vanadium dioxide, stir at 54°C and 300r / min for 4 hours, filter, wash with anhydrous ethanol and deionized water 5 times each, dry at 80°C for 9 hours under vacuum conditions to obtain modified vanadium dioxide; (2) Add phenylboric acid and 3-chloropropylmethyldimethoxysilane in a molar ratio of 1:1.3 to 1,4-dioxane (16 times the mass of phenylboric acid), stir and react at 81°C and 300 r / min for 50 min, add 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane (0.13 times the mass of 3-chloropropylmethyldimethoxysilane), continue stirring and reacting for 8 min, cool to room temperature, wash with an equal volume of toluene and deionized water, stand and separate, take the organic phase, and dry it at 60°C under vacuum for 8 h to obtain borosiloxane oligomer; (3) Mix borosiloxane oligomer, 1,6-hexanediol, dibutyltin dilaurate and butanone in a mass ratio of 1:0.3:0.05:10, stir at 30°C and 200 r / min for 10 min, heat to 78°C, add isophorone diisocyanate in an amount 2.2 times the mass of borosiloxane oligomer, continue stirring and react for 4 h, add anhydrous ethanol in an amount 1.2 times the mass of isophorone diisocyanate, mix evenly, continue stirring for 5 min, and dry at 70°C under vacuum conditions for 10 h to obtain functionalized polyurethane; (4) Functionalized polyurethane and modified vanadium dioxide were added into an internal mixer at a mass ratio of 1:0.05, stirred at 190°C and 80 r / min for 6 min, and placed in a molding machine for compression molding. The upper and lower mold plate temperatures of the molding machine were set to 210°C, the pressure was set to 16 MPa, and the molding time was set to 7 min. After cooling to room temperature, the material was demolded to obtain a phase change temperature-controlled polyurethane material.
[0021] Comparative Example 1: The difference between the preparation method of the phase-change temperature-control polyurethane material of Comparative Example 1 and Example 2 is that step (1) is not performed, and step (4) is modified as follows: functionalized polyurethane and vanadium dioxide are added to an internal mixer at a mass ratio of 1:0.04, stirred at 185°C and 70 r / min for 7 minutes, placed in a molding machine for molding, the upper and lower mold plate temperatures of the molding machine are set to 205°C, the pressure is 15 MPa, the time is 8 minutes, and the mold is demolded after cooling to room temperature to obtain a phase-change temperature-control polyurethane material. The remaining steps are the same as those of Example 2.
[0022] Comparative Example 2: The preparation method of the phase-change temperature-control polyurethane material of Comparative Example 2 is different from that of Example 2 in step (2). Step (2) is modified as follows: phenylboric acid and dimethyldimethoxysilane are added in a molar ratio of 1:1.25 to 1,4-dioxane with a mass of 15 times that of phenylboric acid, stirred at 80°C and 250 r / min for 55 min, 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane with a mass of 0.12 times that of dimethyldimethoxysilane is added, stirred for 9 min, cooled to room temperature, washed with an equal volume of toluene and deionized water, allowed to stand for stratification, the organic phase is taken, and dried at 55°C for 9 h under vacuum to obtain a borosiloxane oligomer. The remaining steps are the same as those of Example 2.
[0023] Comparative Example 3: The preparation method of the phase-change temperature-control polyurethane material of Comparative Example 3 differs from that of Example 2 only in that step (2) is not performed, and step (3) is modified as follows: dihydroxy-terminated polysiloxane, 1,6-hexanediol, dibutyltin dilaurate, and butanone are mixed uniformly in a mass ratio of 1:0.25:0.04:9, stirred at 20°C and 150 r / min for 11 min, heated to 77°C, added with isophorone diisocyanate in an amount 2.1 times the mass of the dihydroxy-terminated polysiloxane, continued to stir for 4.5 h, added with anhydrous ethanol in an amount 1.1 times the mass of the isophorone diisocyanate, mixed uniformly, continued to stir for 6 min, and dried at 69°C for 11 h under vacuum conditions to obtain a functionalized polyurethane; the molecular weight of the dihydroxy-terminated polysiloxane is 2000. The remaining steps are the same as those of Example 2.
[0024] Test Example 1 Energy-saving and temperature-control performance test Test method: The solar film tester produced by Shenzhen Linshang Technology Co., Ltd. was used to test the infrared blocking rate of the embodiment and the comparative example at 20° C. and 90° C. The results are shown in Table 1.
[0025] Table 1
[0026] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the phase-change temperature-controlling polyurethane material prepared by the present invention has good energy-saving and temperature-controlling performance.
[0027] By comparison, the infrared blocking rates of Examples 1 to 3 at 20°C are lower than that of Comparative Example 1 at 20°C, and the infrared blocking rates of Examples 1 to 3 at 90°C are higher than that of Comparative Example 1 at 90°C, indicating that vanadium dioxide is sequentially reacted with 4-anilinotriethoxysilane and N,N-dimethyl-4-nitrosoaniline to obtain modified vanadium dioxide; vanadium dioxide is a thermochromic material that undergoes a reversible phase change at 68°C from an insulating monoclinic phase to a metallic rutile phase, and at the same time, the optical and electrical properties undergo a sharp change, and the infrared transmittance changes from high transmittance at low temperature to high transmittance at low temperature. The reflectivity changes to high reflectivity at high temperature, showing excellent infrared region regulation ability. When glass windows are produced with phase change temperature-control polyurethane materials, the indoor temperature can be kept warm in winter and cool in summer, greatly reducing the energy consumption caused by indoor heating in winter and cooling in summer. Vanadium dioxide is an inorganic material and has poor compatibility with organic polymer material polyurethane. Direct addition will result in uneven distribution and agglomeration of vanadium dioxide. Surface modification of vanadium dioxide is performed to improve the compatibility of vanadium dioxide with polyurethane, so that vanadium dioxide is evenly dispersed in polyurethane, giving full play to the phase change temperature control effect of vanadium dioxide.
[0028] Test Example 2 Testing of mechanical properties and anti-aging properties Test method: Prepare the examples and comparative examples into standard specimens according to GB / T1040, test their tensile strength M, irradiate the standard specimens with a xenon arc lamp for 14 days, test their tensile strength N, and calculate the change rate of tensile strength of the examples and comparative examples before and after ultraviolet aging treatment, tensile strength change rate = (MN) / M × 100%. The results are shown in Table 2 Table 2
[0029] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the phase-change temperature-controlling polyurethane material prepared by the present invention has good mechanical properties and anti-aging properties.
[0030] By comparison, the tensile strength of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that the aniline group introduced on the surface of the pre-modified vanadium dioxide undergoes a Mills reaction with the nitroso group on N,N-dimethyl-4-nitrosoaniline to obtain modified vanadium dioxide, and a tertiary amine structure is introduced on the surface of the modified vanadium dioxide. The tertiary amine structure introduced on the surface of the modified vanadium dioxide can react with the chlorine atom introduced on the side chain of the functionalized polyurethane molecule to generate a quaternary ammonium salt structure, so that a cross-linked structure is formed between the polyurethane molecular chain and the modified vanadium dioxide, thereby inhibiting the relative slip between the polyurethane molecular chains and improving the mechanical properties of the phase change temperature-control polyurethane material.
[0031] By comparison, the tensile strength of Examples 1 to 3 is greater than that of Comparative Examples 2 to 3, indicating that phenylboric acid and 3-chloropropylmethyldimethoxysilane are polymerized and end-capped with 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane to prepare a borosiloxane oligomer, an Si-OB structure is introduced into the main chain of the borosiloxane oligomer molecule, a chlorine atom is introduced into the side chain of the borosiloxane oligomer molecule, and hydroxyl groups are introduced into both ends of the borosiloxane oligomer molecular chain; the hydroxyl groups introduced into both ends of the borosiloxane oligomer molecular chain enable it to participate in the polymerization reaction of the polyurethane; the borosiloxane oligomer, 1,6-hexanediol and isophorone diisocyanate are reacted to obtain a polyurethane. Functionalized polyurethane is prepared by polymerization of acid esters; Si-OB structure is introduced into the main chain of functionalized polyurethane molecule, and chlorine atoms are introduced into the side chain of functionalized polyurethane molecule; the chlorine atoms introduced into the side chain of functionalized polyurethane molecule can react with the tertiary amine structure on modified vanadium dioxide to form a cross-linked network, thereby improving the mechanical properties of phase-change temperature-control polyurethane material; the tensile strength of comparative example 2 is greater than the tensile strength of comparative example 3, indicating that boron-oxygen coordination bonds can be formed between the boron atoms of Si-OB in the main chain and the oxygen atoms in the adjacent molecular chains, and the formation of boron-oxygen coordination bonds also causes physical cross-linking between polyurethane molecular chains, thereby further improving the mechanical properties of phase-change temperature-control polyurethane material.
[0032] By comparison, the change rate of tensile strength of Examples 1 to 3 is less than the change rate of tensile strength of Comparative Example 1, indicating that vanadium dioxide and 4-anilinotriethoxysilane are reacted to obtain pre-modified vanadium dioxide, and aniline groups are introduced on the surface of the pre-modified vanadium dioxide; the aniline groups introduced on the surface of the pre-modified vanadium dioxide undergo a Mills reaction with the nitroso groups on N,N-dimethyl-4-nitrosoaniline to obtain modified vanadium dioxide, and an azobenzene structure is generated on the surface of the modified vanadium dioxide; the azobenzene structure is transformed from a trans conformation to a cis conformation under the action of ultraviolet light, and is transformed from a cis conformation to a trans conformation under the irradiation of visible light with a wavelength greater than 440 nm. This reversible conformational change can absorb ultraviolet light, thereby giving the phase-change temperature-control polyurethane material excellent anti-aging properties.
[0033] Test Example 3 Testing of self-healing properties Test method: The embodiment and the comparative example are prepared into standard specimens according to GB / T1040, and the tensile strength X of the standard specimens is tested; a slit with a depth of 2 mm and a length of 18 mm is cut from the middle of the original unstretched standard specimen, placed in a mold, and left to stand at 30°C for 24 hours to obtain a healed standard specimen, and its tensile strength Y is tested by a tensile machine; the self-healing rate of the embodiment and the comparative example is calculated, and the self-healing rate = (tensile strength Y of the healed standard specimen / original tensile strength X of the standard specimen) × 100%. The results are shown in Table 3.
[0034] Table 3
[0035] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the phase-change temperature-controlling polyurethane material prepared by the present invention has good self-healing performance.
[0036] By comparison, the self-healing rates of Examples 1 to 3 are greater than that of Comparative Example 3, indicating that phenylboric acid and 3-chloropropylmethyldimethoxysilane are polymerized and end-capped with 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane to prepare a borosiloxane oligomer, an Si-OB structure is introduced into the main chain of the borosiloxane oligomer molecule, and hydroxyl groups are introduced at both ends of the borosiloxane oligomer molecular chain; the hydroxyl groups introduced at both ends of the borosiloxane oligomer molecular chain enable it to participate in the polymerization reaction of the polyurethane; the borosiloxane oligomer, 1,6-hexanediol and isophorone diisocyanate are reacted to form a polyurethane polymerization reaction; Functionalized polyurethane is prepared by polymerization of acid esters; Si-OB structure is introduced into the main chain of functionalized polyurethane molecule, and boron-oxygen coordination bond can be formed between the boron atom of Si-OB in the main chain and the oxygen atom in the adjacent molecular chain. The boron-oxygen coordination bond is a dynamic reversible bond. The boron atom with vacancy acts as an acceptor of the lone electron pair of oxygen atom in the adjacent molecular chain, forming a non-bonded complex between molecules. The interaction between boron and oxygen atoms causes dynamic physical cross-linking between molecular chains. The bonding action is in a dynamic process of continuous dissociation and reformation, thereby making the phase change temperature-controlled polyurethane material have self-healing properties.
[0037] Test Example 4 Antibacterial performance test Test method: The examples and comparative examples were cut into 18 mm × 18 mm × 6 mm samples and sterilized by ultraviolet irradiation for 8 h; the Escherichia coli strains were activated and prepared to a concentration of 3 × 10 4 cfu / ml bacterial suspension; put the sample into the bacterial suspension, shake at 200r / min for 10min at room temperature, take 1ml of the bacterial suspension and dilute it to 100 times, take 1ml of the diluted bacterial suspension and inoculate it into agar medium, culture it at 37℃ for 16h, count the colonies according to the method in GB / T15979, and calculate the antibacterial rate. The results are shown in Table 4.
[0038] Table 4
[0039] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 4, it can be found that the phase-change temperature-control polyurethane material prepared by the present invention has good antibacterial properties.
[0040] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that the aniline group introduced on the surface of the pre-modified vanadium dioxide undergoes a Mills reaction with the nitroso group on N,N-dimethyl-4-nitrosoaniline to obtain modified vanadium dioxide, and a tertiary amine structure is introduced on the surface of the modified vanadium dioxide. The tertiary amine structure introduced on the surface of the modified vanadium dioxide can react with the chlorine atom introduced on the side chain of the functionalized polyurethane molecule to generate a quaternary ammonium salt structure. The generated quaternary ammonium salt structure has an antibacterial effect and can give the phase change temperature-control polyurethane material excellent antibacterial properties.
[0041] By comparison, the antibacterial rates of Examples 1 to 3 are greater than those of Comparative Examples 2 to 3, indicating that phenylboric acid and 3-chloropropylmethyldimethoxysilane are polymerized and terminated with 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane to obtain a borosiloxane oligomer, chlorine atoms are introduced into the side chains of the borosiloxane oligomer molecules, and hydroxyl groups are introduced into both ends of the borosiloxane oligomer molecular chains; the hydroxyl groups introduced into both ends of the borosiloxane oligomer molecular chains enable the borosiloxane oligomer to participate in the polymerization reaction of polyurethane; borosiloxane oligomer, 1,6-hexanediol and isophorone diisocyanate are polymerized to obtain a functionalized polyurethane; chlorine atoms are introduced into the side chains of the functionalized polyurethane molecules; the chlorine atoms introduced into the side chains of the functionalized polyurethane molecules can react with the tertiary amine introduced into the modified vanadium dioxide to generate a quaternary ammonium salt structure, and the generated quaternary ammonium salt structure has an antibacterial effect, and can give the phase change temperature-control polyurethane material excellent antibacterial properties.
[0042] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A phase-change temperature-control polyurethane material, characterized in that: The phase-change temperature-control polyurethane material is prepared by reacting pre-modified vanadium dioxide and N,N-dimethyl-4-nitrosoaniline to obtain modified vanadium dioxide; polymerizing borosiloxane oligomer, 1,6-hexanediol and isophorone diisocyanate to obtain functional polyurethane; and uniformly mixing the functional polyurethane and the modified vanadium dioxide, and performing compression molding. The pre-modified vanadium dioxide is prepared by reacting vanadium dioxide and 4-anilinotriethoxysilane; The borosiloxane oligomer is prepared by polymerizing phenylboric acid and 3-chloropropylmethyldimethoxysilane and capping with 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane.
2. A method for preparing a phase-change temperature-controlling polyurethane material, characterized in that: The preparation method of the phase-change temperature-controlling polyurethane material comprises the following preparation steps: (1) Pre-modified vanadium dioxide, glacial acetic acid, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(0.6-0.8):(40-50), and ultrasonically dispersed for 20-30 min. N,N-dimethyl-4-nitrosoaniline (3-4 times the mass of the pre-modified vanadium dioxide) was added, and stirred at 50-54°C and 200-300 r / min for 4-5 h. The mixture was filtered, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 70-80°C under vacuum conditions for 9-10 h to obtain modified vanadium dioxide. (2) Add phenylboric acid and 3-chloropropylmethyldimethoxysilane in a molar ratio of 1:(1.2~1.3) to 1,4-dioxane (14~16 times the mass of phenylboric acid), stir and react at 79~81°C and 200~300r / min for 50~60min, add a capping agent (0.11~0.13 times the mass of 3-chloropropylmethyldimethoxysilane), continue stirring and reacting for 8~10min, cool to room temperature, wash with an equal volume of toluene and deionized water, stand for stratification, take the organic phase, and dry it at 50~60°C under vacuum conditions for 8~10h to obtain borosiloxane oligomer; (3) Mix borosiloxane oligomer, 1,6-hexanediol, dibutyltin dilaurate and butanone evenly, stir at 10-30°C and 100-200 r / min for 10-12 min, heat to 76-78°C, add isophorone diisocyanate in an amount of 2-2.2 times the mass of borosiloxane oligomer, continue stirring and reacting for 4-5 h, add anhydrous ethanol in an amount of 1-1.2 times the mass of isophorone diisocyanate, mix evenly, continue stirring for 5-7 min, and dry at 68-70°C under vacuum conditions for 10-12 h to obtain functionalized polyurethane; (4) Add functionalized polyurethane and modified vanadium dioxide into an internal mixer at a mass ratio of 1:(0.03-0.05), stir at 180-190°C and 60-80 r / min for 6-8 min, place in a molding machine for compression molding, cool to room temperature and then demold, to obtain a phase change temperature-controlled polyurethane material.
3. The method for preparing a phase-change temperature-controlling polyurethane material according to claim 2, characterized in that: The preparation method of the pre-modified vanadium dioxide in step (1) is as follows: vanadium dioxide and anhydrous ethanol are mixed uniformly in a mass ratio of 1:(60~70), ultrasonically dispersed for 1.2~1.4h, 7~8 times the mass of vanadium dioxide is added with anilinosilane hydrolyzate, stirred at 50~60°C and 100~200r / min for 2~2.2h, filtered, washed with anhydrous ethanol for 3~5 times, and dried at 60~70°C under vacuum conditions for 9~10h to obtain pre-modified vanadium dioxide.
4. The method for preparing a phase-change temperature-controlling polyurethane material according to claim 3, characterized in that: The particle size of the vanadium dioxide is 2000 meshes.
5. The method for preparing a phase-change temperature-controlling polyurethane material according to claim 3, characterized in that: The preparation method of the anilinosilane hydrolyzate is as follows: 4-anilinotriethoxysilane and deionized water are uniformly mixed in a mass ratio of 1:(20-22), stirred at 10-30° C. and 100-200 r / min for 10-12 min, adjusted the pH to 5.6-5.8 with an oxalic acid aqueous solution, and continued stirring for 20-30 min to prepare the anilinosilane hydrolyzate.
6. The method for preparing a phase-change temperature-controlling polyurethane material according to claim 5, characterized in that: The concentration of the oxalic acid aqueous solution is 1 mol / L.
7. The method for preparing a phase-change temperature-controlling polyurethane material according to claim 2, characterized in that: The capping agent in step (2) is: 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane.
8. The method for preparing a phase-change temperature-controlling polyurethane material according to claim 2, characterized in that: The mass ratio of the borosiloxane oligomer, 1,6-hexanediol, dibutyltin dilaurate and butanone in step (3) is 1:(0.2-0.3):(0.03-0.05):(8-10).
9. The method for preparing a phase-change temperature-controlling polyurethane material according to claim 2, characterized in that: The process parameters of the compression molding in step (4) are as follows: setting the temperature of the upper and lower mold plates of the compression molding machine to 200-210° C., the pressure to 14-16 MPa, and the time to 7-9 min.
Citation Information
Patent Citations
Vanadium dioxide intelligent temperature control coating
CN103073943A
Method for preparing intelligent temperature-controlpolyester chip with in-situ polymerization method
CN104479117A
Thermal insulation coating and preparation method thereof
CN104893550A
Dynamic polymer foam composite material[v]
CN111253610A
Environment-friendly polyurethane foaming agent and preparation method thereof
CN112300435A